Impact of double-bolus tracking to individualize scan timing of the portal venous phase in preoperative computed tomography colonography angiography for right-sided colon cancer - Yoshiya Ohashi; Masaaki Miyo; Koichi Okuya; Emi Akizuki; Atsushi Hamabe; Ai Noda; Masayuki Ishii; Ryo Miura; Momoko Ichihara; Maho Toyota; Kohei Okamoto; Shun Hayasaka; et al. (PLoS ONE, 2025)
Aim In computed tomography colonography angiography (CTC-A), used for preoperative screening of right-sided colon cancer, the timing of venous phase imaging is conventionally determined by a fixed-delay time; however, the contrast effect may be insufficient because of individual differences in blood flow status. Therefore, we developed the double-bolus tracking (DBT) method to solve this issue. Method We compared the contrast effect and image quality of the portal venous systems between two methods of the conventional fixed-delay and DBT which utilizes low-dose monitoring to individualize venous scan timings. Data from 30 consecutive patients who underwent CTC-A for right-sided colon cancer using the DBT method were prospectively collected and compared with that from 30 consecutive patients who underwent the conventional fixed-delay method between August 2018 and July 2022. CT values of the portal vein, gastrocolic trunk, and middle colic veins were measured. Additionally, two gastrointestinal surgeons performed a five-point visual evaluation of the three-dimensional volume rendering image of the gastrocolic trunk. Results CT values in the DBT group were significantly higher than those in the fixed-delay group. (portal vein: 266.7 HU vs. 210.0 HU; p <  0.001, gastrocolic trunk: 251.6 HU vs. 191.0 HU; p <  0.001, middle colic vein: 257.2 HU vs. 190.1 HU; p <  0.001). Visual assessment of the gastrocolic trunk was significantly higher in the DBT group than that in the fixed-delay group (DBT, 3.6, 3.4; fixed-delay, 2.6, 2.8; p =  0.003, p =  0.044). Conclusion The DBT method can enhance the contrast effect of the portal venous systems and improve image quality.